2019
DOI: 10.3390/ijms20194957
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Inflammation by Flavonoids: Novel Therapeutic Strategy for Metabolic Disorders

Abstract: A balanced metabolic profile is essential for normal human physiological activities. Disproportions in nutrition give rise to imbalances in metabolism that are associated with aberrant immune function and an elevated risk for inflammatory-associated disorders. Inflammation is a complex process, and numerous mediators affect inflammation-mediated disorders. The available clinical modalities do not effectively address the underlying diseases but rather relieve the symptoms. Therefore, novel targeted agents have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 290 publications
0
57
0
Order By: Relevance
“…After the intervention period, significantly reduced levels of glycosylated hemoglobin (HbA1c) were found in the almond group [62]. According to the authors, the observed hypoglycemic effect of almonds might be due to the slowing of gastric emptying (as a consequence of the fat and protein contained in the nuts), but also to the presence of polyphenols, mainly flavonoids, that help control glucose blood levels [62,84], inhibiting amylase [62]. Interestingly, flavonoids are effective ay inhibiting the activity of salivary amylase, which represents a remarkable target for glycemic control in diabetics since in this class of patients the activity of pancreatic amylase is strongly reduced (28% to 35%) [85,86].…”
Section: Glycemic Controlmentioning
confidence: 99%
“…After the intervention period, significantly reduced levels of glycosylated hemoglobin (HbA1c) were found in the almond group [62]. According to the authors, the observed hypoglycemic effect of almonds might be due to the slowing of gastric emptying (as a consequence of the fat and protein contained in the nuts), but also to the presence of polyphenols, mainly flavonoids, that help control glucose blood levels [62,84], inhibiting amylase [62]. Interestingly, flavonoids are effective ay inhibiting the activity of salivary amylase, which represents a remarkable target for glycemic control in diabetics since in this class of patients the activity of pancreatic amylase is strongly reduced (28% to 35%) [85,86].…”
Section: Glycemic Controlmentioning
confidence: 99%
“…Many clinical interventions suggested that dietary almond through multiple mechanisms of actions, i.e., reducing glycemic index value of coconsumed food, increasing insulin secretion, and alleviating insulin resistance controls diabetes [40,43]. It is also suggested that the polyphenols mainly flavonoids present in almond also controls blood glucose levels by the action of inhibiting amylase which is a carbohydrate digestive enzyme [40,44].…”
Section: Almond and Diabetesmentioning
confidence: 99%
“…Our group has shown the presence of substantial amounts of kaempferol and crocin ( Figure 1) in saffron petals [15,16] which make up the bulk of the flowers, but are currently considered a waste material. Kaempferol is one of the main flavonols of the saffron spice and has protective properties against lipid oxidation, which contributes to the onset and progression of atherosclerosis and cardiovascular diseases [7,8]. Originally derived from the carotenoid crocetin, crocins have a common structural feature of digentiobiose esters [19].…”
Section: Introductionmentioning
confidence: 99%